al Kutub al Jàwiyah al Mathbù'ah fi Makkah al Mukarramah min Awàkhir al Qorn al Tàsi' 'Ashr ilà Awà'il al Qarn al 'Ishrìn al Mìlàdiy - Sya'ban, A Ginanjar (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2020)
This article intends to examine the histories of the printing of the "Jawikitabs” in Mecca and the ulama of Archipelago (Jawi) taught in Mecca and published their works there. The Jawi kitabs printed and spread in the holy city, Mecca, while the ulamas of the Archipelago (Jawi) are from the late 19th century into the early 20thcentury (1885 to 1909, to be precise). This period coincided with the last period of the Ottoman dynasty's rule over Mecca and other Hijaz regions. The approach used in this study is a historiography and regional bibliography approach. The finding of thisresearch is that among the Nusantara Ulamas who had published their work in Mecca are SyaikhNuruddin al-Raniri, Syaikh Abdul Rauf Singkel, Syaikh Muhammad Zain Aceh, Syaikh Arsyad Banjar, Syaikh Abdul Shamad Palembang, Syaikh Dawud Pattani, Syaikh NawawiBanten, Syaikh Zainuddin Sumbawa, Syaikh Ahmad Khatib Minangkabau, Syaikh Ahmad Pattani, Syaikh Mahfuzh Tremas, Syaikh Ahmad Muhtarom Banyumas, Syaikh Mukhtar Bogor.